The Community Participation in the Environmental Management of Used Battery Smelting Activities - Sodikin, Sodikin; Permana, Divia Rekha (Jurnal Daulat Hukum, 2023)
Article 70 of Law Number 32 of 2009 provides concrete directions, instructions and forms of community participation in environmental protection and management. The participation includes forms of efforts that can be done by the community so that they can participate in protecting and managing their environment. The manifestation of such participation can be in the form of social supervision, giving advice, opinions, proposals, objections, complaints, submitting information and reports. The manifestation of community participation in the Cinangka village is related to the smelting of used batteries which has the effect of environmental pollution which greatly disrupts the life of the Cinangka village community in various ways as directed in Article 70 of Law Number 32 Year 2009. The form of participation was carried out with the submission of complaints to the Village Government to the Bogor Regency Environmental Agency, demonstrations, deliberations with business actors for the use of smelting used batteries, conducting legal proceedings against business actors, and participating in the success of the Eco-Friendly Village program. Because the legal awareness of the community is still low which is influenced by low educational factors, so not all people participate in participating in environmental management.